Porous carbon with secondary particle configuration, preparation method and application thereof, gas phase silicon carbon material and application thereof
By adopting the porous carbon preparation method with secondary particle configuration, the problems of limited expansion improvement and rate improvement of existing gas-phase silicon carbon materials are solved, and the low expansion and high rate performance of lithium-ion secondary batteries are achieved.
Patent Information
- Application Number
- CN202411640797.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing gas-phase silicon carbon materials have a single-particle structure, which leads to improvement in expansion and limited magnification, which limits their application in terminal products.
The porous carbon preparation method with secondary particle configuration is adopted to generate primary particles through carbon source polymerization, and the secondary particle hard carbon precursor is melted and formed, followed by pyrolytic carbonization and activation treatment to obtain low expansion and high magnification gas phase silicon carbon material.
It effectively reduces the charging volume expansion of lithium-ion secondary batteries, significantly improves the rate performance of lithium-ion secondary batteries, and realizes the characteristics of low expansion and high magnification.
Smart Images

Figure CN119143129B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of porous carbon, and in particular to a porous carbon with a secondary particle configuration, a preparation method and application thereof, and a gas phase silicon carbon material and application thereof. Background Art
[0002] With the development of consumer electronics, new energy vehicles and electric aircraft, the market demand for high energy density electrode materials is becoming more and more urgent. Silicon material has a theoretical capacity of up to 4200mA·h / g, and can be alloyed to form Li 15 Si4, its gram capacity can reach 3579mA·h / g. Therefore, the application of silicon materials to the negative electrode of the battery is conducive to greatly improving the energy density of the battery. The silicon inside the gas phase silicon carbon can be evenly distributed in the porous carbon in the form of dispersed small particles, and the electrochemical performance is significantly improved, which has great development potential.
[0003] However, the existing gas-phase silicon-carbon materials are all single-particle structures. The expansion and contraction of a single particle during charging and discharging are large, and the lithium ion transmission path is long. The potential for further improvement in expansion and rate performance is limited, which limits their application in terminal products.
[0004] The final particle morphology of gas phase silicon carbon materials is determined by porous carbon, and the existing porous carbon used for gas phase silicon carbon materials is in single particle form. At present, it is urgent to develop porous carbon with secondary particle configuration.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the purposes of the present invention is to provide a method for preparing porous carbon with a secondary particle configuration, which has a simple process, high efficiency, high success rate and is suitable for industrial production.
[0007] The second purpose of the present invention is to provide a porous carbon with a secondary particle configuration, which can solve the technical problem that the existing gas phase silicon carbon materials are difficult to effectively improve the expansion and significantly increase the rate due to the porous carbon having a single particle structure.
[0008] The third purpose of the present invention is to provide an application of porous carbon with a secondary particle configuration, which solves the technical problems of limited expansion improvement and rate enhancement of existing gas-phase silicon-carbon materials.
[0009] A fourth object of the present invention is to provide a gas phase silicon carbon material having the characteristics of low expansion and high ratio.
[0010] A fifth object of the present invention is to provide an application of a gas phase silicon carbon material, which can effectively reduce the charging volume expansion of a lithium ion secondary battery and significantly improve the rate performance of the lithium ion secondary battery.
[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0012] In a first aspect, a method for preparing porous carbon of a secondary particle configuration comprises the following steps:
[0013] (a) subjecting the carbon source to polymerization reaction to generate primary particles, which are then fused to obtain secondary particles of hard carbon precursor;
[0014] (b) The secondary particle hard carbon precursor of step (a) is first subjected to pyrolysis and carbonization, and then subjected to activation treatment to obtain porous carbon with the secondary particle configuration.
[0015] Further, the carbon source includes at least one of glucose, fructose, galactose, lactose, sucrose, maltose, rice starch, mung bean starch, wheat starch, cassava starch, corn starch, cellulose and phenolic resin;
[0016] The additives used in the polymerization reaction include at least one of maleic anhydride, hydroxymethyl cellulose, sodium hexametaphosphate, sodium lauryl sulfate, polyvinyl alcohol, hexadecyltrimethylammonium bromide and polyvinyl pyrrolidone;
[0017] The amount of the additive is 0.01% to 0.5% of the weight of the carbon source;
[0018] The polymerization reaction temperature is 150°C to 350°C;
[0019] The polymerization reaction pressure is 2Mpa~8Mpa.
[0020] Furthermore, the particle size of the primary particles is 20% to 50% of the particle size of the secondary particles;
[0021] The average sphericity of the primary particles is 0.6 to 1.0;
[0022] The D50 particle size of the primary particles is 0.6 μm to 7.5 μm.
[0023] Furthermore, the temperature of the pyrolysis carbonization is 800°C to 1400°C, and the time of the pyrolysis carbonization is 1h to 12h;
[0024] The activation treatment method includes at least one of a physical activation method and a chemical activation method;
[0025] The gas used in the physical activation method includes at least one of water vapor, air and carbon dioxide.
[0026] In a second aspect, a porous carbon with a secondary particle configuration is prepared by any of the preparation methods described above.
[0027] In a third aspect, a porous carbon having the secondary particle configuration described above is used in a gas phase silicon-carbon material.
[0028] Furthermore, the specific surface area of the porous carbon of the secondary particle configuration is 700 m 2 / g~2000m 2 / g, pore volume is 0.3cm 3 / g~1.2cm 3 / g.
[0029] Furthermore, the D50 particle size of the porous carbon of the secondary particle configuration is 3 μm to 15 μm;
[0030] The particle size distribution K90 of the porous carbon with the secondary particle configuration is 0.8~1.8.
[0031] In a fourth aspect, a gas phase silicon carbon material is formed by depositing nano-silicon on the porous carbon with the secondary particle configuration described above.
[0032] A fifth aspect is an application of the above-mentioned gas phase silicon carbon material in a lithium ion secondary battery.
[0033] Compared with the prior art, the present invention has at least the following beneficial effects:
[0034] The method for preparing the porous carbon with a secondary particle configuration provided by the present invention has a simple process, high efficiency, high success rate, and is suitable for industrial production.
[0035] The porous carbon with a secondary particle configuration provided by the present invention can solve the technical problem that the existing gas phase silicon carbon materials are difficult to effectively improve the expansion and significantly increase the rate due to the porous carbon having a single particle structure.
[0036] The application of the porous carbon with a secondary particle configuration provided by the present invention can effectively reduce the expansion of silicon-carbon materials and significantly improve the rate performance of silicon-carbon materials due to the secondary granulation configuration of the porous carbon. The mechanism lies in that the expansion of the primary particles in the secondary particles is isotropic and they restrict the expansion of each other, thereby reflecting that the expansion of the apparent single secondary particles is reduced. In addition, there are gaps between the particles, so the overall expansion of the silicon-carbon material is significantly reduced. At the same time, since the contact area between the secondary particles and the electrolyte is large and the transmission path of lithium ions is short, the rate performance of the silicon-carbon material can be improved. In short, the present invention solves the technical problem that the existing gas-phase silicon-carbon materials have limited expansion improvement and rate improvement due to their single particle structure, and achieves the technical effect of effectively reducing the charging volume expansion and significantly improving the rate performance.
[0037] The gas phase silicon carbon material provided by the present invention effectively reduces the volume expansion during charging, while improving the rate performance, and has the characteristics of low expansion and high rate.
[0038] The application of the gas phase silicon carbon material provided by the present invention can effectively reduce the charging volume expansion of the lithium ion secondary battery, significantly improve the rate performance of the lithium ion secondary battery, and has an outstanding application effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 A 10,000-fold scanning electron microscope image of the porous carbon having a secondary particle configuration provided in Example 1 of the present invention;
[0041] Figure 2 A 20,000-fold scanning electron microscope image of the gas phase silicon carbon material provided in Example 1 of the present invention;
[0042] Figure 3 The first charge and discharge curve of the lithium button cell made of the gas phase silicon carbon material obtained in Example 1 of the present invention;
[0043] Figure 4 This is a dQ / dV curve of the first charge and discharge of the lithium button cell made of the gas phase silicon carbon material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0044] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] According to a first aspect of the present invention, there is provided a method for preparing porous carbon in a secondary particle configuration, comprising the following steps:
[0046] (a) subjecting the carbon source to polymerization reaction to generate primary particles, which are then fused to obtain secondary particles of hard carbon precursor;
[0047] (b) The secondary particle hard carbon precursor of step (a) is first subjected to pyrolysis and carbonization, and then subjected to activation treatment to obtain porous carbon with a secondary particle configuration.
[0048] The method for preparing the porous carbon with a secondary particle configuration provided by the present invention has a simple process, high efficiency, high success rate, and is suitable for industrial production.
[0049] In the present invention, the method for preparing the secondary particle hard carbon precursor comprises the following steps:
[0050] The carbon source, additives and water are mixed and reacted to polymerize the carbon source. During the polymerization reaction, primary particles with a particle size of 0.6μm~7.5μm are first generated. The incompletely solidified primary particles will collide with each other under stirring, and the particles will fuse to obtain secondary particles of hard carbon precursor.
[0051] In a preferred embodiment, the carbon source includes but is not limited to at least one of glucose, fructose, galactose, lactose, sucrose, maltose, rice starch, mung bean starch, wheat starch, tapioca starch, corn starch, cellulose and phenolic resin.
[0052] In a preferred embodiment, the additives include but are not limited to at least one of maleic anhydride, hydroxymethyl cellulose, sodium hexametaphosphate, sodium dodecyl sulfate, polyvinyl alcohol, hexadecyltrimethylammonium bromide and polyvinyl pyrrolidone. The additives can regulate the particle size of the primary particles through electrostatic repulsion and steric hindrance, and then merge into the desired secondary particles.
[0053] In the present invention, the amount of the additive can be 0.01%~0.5% of the weight of the carbon source, for example, it can be 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, but not limited to this. The appropriate amount of the additive is more conducive to improving the formation effect of primary particles and secondary particles of a specific particle size; if the amount of the additive is too small, the configuration of the secondary particles cannot be effectively formed; if the amount of the additive is too much, the particle size of the primary particles formed is too small, which will result in a lower primary efficiency of the material.
[0054] In a preferred embodiment, the polymerization reaction temperature can be 150°C ~ 350°C, and typical but non-limiting temperatures are, for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 325°C, 350°C; the polymerization reaction pressure can be 2Mpa ~ 8Mpa, and typical but non-limiting pressures are, for example, 2Mpa, 3Mpa, 4Mpa, 5Mpa, 6Mpa, 7Mpa, 8Mpa.
[0055] Appropriate temperature and pressure of the polymerization reaction are more conducive to further improving the formation effect of secondary particles and spherical morphology; if the temperature and / or pressure of the polymerization reaction is too low, the supercritical state cannot be formed, resulting in difficulty in conducting the polymerization reaction; if the temperature and / or pressure of the polymerization reaction is too high, the polymerization reaction rate will be too fast, resulting in only a single particle structure being formed, and it is difficult to form a secondary particle structure.
[0056] In a preferred embodiment, the temperature for pyrolysis carbonization of the secondary particle hard carbon precursor can be 800℃~1400℃, and typical but non-limiting temperatures are 800℃, 900℃, 1000℃, 1100℃, 1200℃, 1300℃, and 1400℃; the time for pyrolysis carbonization can be 1h~12h, and typical but non-limiting times are 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, and 12h.
[0057] The appropriate temperature and time of pyrolysis carbonization are more conducive to improving the formation effect of porous carbon materials; if the temperature of pyrolysis carbonization is too high and / or the time is too long, the resulting structure will be too dense, resulting in difficulty in subsequent activation and pore formation; if the temperature of pyrolysis carbonization is too low and / or the time is too short, the active groups will not be completely removed, resulting in more side reactions in the battery.
[0058] In a preferred embodiment, the activation treatment method can be at least one of a physical activation method and a chemical activation method; wherein the gas used in the physical activation method includes but is not limited to at least one of water vapor, air and carbon dioxide, which is more conducive to further improving the effect of the activation treatment.
[0059] A typical method for preparing porous carbon of secondary particle configuration comprises the following steps:
[0060] (1) A carbon source, an additive and water are mixed and reacted to polymerize the carbon source. During the polymerization reaction, primary particles with a particle size of 0.6 μm to 7.5 μm are first generated, and then the primary particles are fused to obtain secondary particles of hard carbon precursor;
[0061] (2) pyrolyzing and carbonizing the secondary particle hard carbon precursor of step (1) to obtain secondary particle hard carbon, i.e., porous carbon precursor;
[0062] (3) Activating the porous carbon precursor of step (2) to obtain porous carbon with a secondary particle configuration.
[0063] According to a second aspect of the present invention, there is provided a porous carbon with a secondary particle configuration, which is prepared by any of the preparation methods described above.
[0064] The porous carbon with a secondary particle configuration provided by the present invention can solve the technical problem that the existing gas phase silicon carbon materials are difficult to effectively improve the expansion and significantly increase the rate due to the porous carbon having a single particle structure.
[0065] According to a third aspect of the present invention, there is provided an application of the porous carbon with the secondary particle configuration described above in a gas phase silicon-carbon material.
[0066] The application of the porous carbon with a secondary particle configuration provided by the present invention can effectively reduce the expansion of silicon-carbon materials and significantly improve the rate performance of silicon-carbon materials due to the secondary granulation configuration. The mechanism lies in that the expansion of primary particles in the secondary particles is isotropic and they restrict each other's expansion, thereby reducing the apparent expansion of a single secondary particle. In addition, there are gaps between the particles, so the overall expansion of the silicon-carbon material is significantly reduced. At the same time, since the contact area between the secondary particles and the electrolyte is large and the transmission path of lithium ions is short, the rate performance of the silicon-carbon material can be improved.
[0067] In summary, the present invention solves the technical problem that the existing gas-phase silicon-carbon materials have limited expansion improvement and rate increase due to the single-particle structure of the porous carbon, and achieves the technical effect of effectively reducing the charging volume expansion and significantly improving the rate performance.
[0068] In a preferred embodiment, the specific surface area of the porous carbon in the secondary particle configuration can be 700 m 2 / g~2000m 2 / g, with a typical but non-limiting specific surface area of, for example, 700 m 2 / g、800m 2 / g、900m 2 / g、1000m 2 / g、1200m 2 / g、1400m 2 / g、1600m 2 / g、1800m 2 / g, 2000m 2 / g; the pore volume of the porous carbon with secondary particle configuration can be 0.3cm 3 / g~1.2cm 3 / g, with a typical but non-limiting pore volume of 0.3 cm 3 / g, 0.4cm 3 / g, 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1cm 3 / g, 1.1cm 3 / g, 1.2cm 3 / g.
[0069] In a preferred embodiment, the D50 particle size of the porous carbon with secondary particle configuration can be 3μm~15μm, and its typical but non-limiting D50 particle size is, for example, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, and 15μm.
[0070] In the present invention, the particle size distribution K90 of the porous carbon with secondary particle configuration can be 0.8-1.8, for example, 0.8, 0.9, 1, 1.2, 1.4, 1.6, 1.8, but not limited thereto.
[0071] It should be noted that the secondary particles are formed by the fusion of spherical primary particles, and the particle size of the primary particles can be 20% to 50% of the particle size of the secondary particles, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, but not limited to this.
[0072] The spherical particle morphology of the primary particles is more conducive to the formation of a dense and uniform SEI film, thereby improving the electrochemical properties of silicon-carbon materials.
[0073] In a preferred embodiment, the average sphericity of the primary particles may be 0.6-1.0, and typical but non-limiting average sphericity is, for example, 0.6, 0.7, 0.8, 0.9, and 1.0, which can further form a dense and uniform SEI film.
[0074] In the present invention, the D50 particle size of the primary particles can be 0.6μm~7.5μm, for example, 0.6μm, 0.8μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, but is not limited to this.
[0075] It should be noted that if the particle size of the primary particles is too small, the surface area will be too large, resulting in more side reactions, which will reduce the initial effect and storage properties of the silicon-carbon material. At the same time, the connections between the primary particles are thin, and the particles are easy to fall off and fail after expansion; if the particle size of the primary particles is too large, it will be difficult to form a secondary particle granulation structure, which is not conducive to improving the expansion and rate properties of the silicon-carbon material.
[0076] In summary, the specific surface area, pore volume, average particle size D50 and particle size distribution K90 of the porous carbon of the secondary particle configuration selected in the present invention, as well as the average particle size D50 and average sphericity of the primary particles, under the action of various specific parameters, can further reduce the charging volume expansion of the silicon-carbon material and further improve the rate performance of the silicon-carbon material.
[0077] According to a fourth aspect of the present invention, there is provided a gas phase silicon carbon material, which is formed by depositing nano-silicon on the porous carbon of the secondary particle configuration described above.
[0078] In the present invention, the porous carbon with secondary particle configuration can adsorb silane compounds and undergo pyrolysis treatment, thereby allowing nano-silicon to be deposited on the porous carbon; in addition, it can also adsorb carbon source gas and undergo pyrolysis treatment, thereby achieving carbon coating and obtaining a gas-phase silicon-carbon material.
[0079] The gas phase silicon carbon material provided by the present invention effectively reduces the volume expansion during charging, while improving the rate performance, and has the characteristics of low expansion and high rate.
[0080] According to a fifth aspect of the present invention, there is provided a use of the above-mentioned gas phase silicon carbon material in a lithium ion secondary battery.
[0081] The application of the gas phase silicon carbon material provided by the present invention can effectively reduce the charging volume expansion of the lithium ion secondary battery, significantly improve the rate performance of the lithium ion secondary battery, and has an outstanding application effect.
[0082] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0083] Example 1
[0084] A method for preparing a gas phase silicon-carbon material comprises the following steps:
[0085] S1: 20 kg sucrose (carbon source), 40 g polyvinyl alcohol (additive) and 100 kg pure water were mixed in a high-pressure reactor and polymerized at 180 ° C for 2 hours. During the polymerization process, primary particles were generated first, and the incompletely solidified primary particles collided with each other under stirring, and the particles merged to obtain secondary particles of hard carbon precursor;
[0086] S2: The secondary particle hard carbon precursor is first subjected to high temperature carbonization at 900°C for 4 hours in a nitrogen atmosphere, and then subjected to air flow pulverization to obtain secondary particle hard carbon, i.e., porous carbon precursor;
[0087] S3: The porous carbon precursor is introduced into carbon dioxide in a rotary kiln for high temperature activation at 900°C for 12 hours to obtain porous carbon with secondary particle configuration;
[0088] S4: The porous carbon with secondary particle configuration is pyrolyzed with monosilane at 500°C for 4 hours in a CVD furnace to deposit nano-silicon in the pore structure of the porous carbon. Acetylene is then introduced at 550°C for 2 hours to perform carbon coating treatment to obtain a gas phase silicon-carbon material.
[0089] The physical and chemical parameters of the porous carbon with secondary particle configuration obtained in this embodiment are shown in Table 1, and its 10000 times scanning electron microscope image is shown in Figure 1 ; The 20000 times scanning electron microscope image of the gas phase silicon carbon material obtained in this embodiment is shown in Figure 2 .
[0090] Example 2
[0091] The difference between this embodiment and embodiment 1 is that in step S1, sucrose is replaced with glucose;
[0092] The remaining steps and their parameters are as in Example 1, and porous carbon with secondary particle configuration and corresponding gas phase silicon carbon material are obtained. The physical and chemical index parameters are shown in Table 1.
[0093] Example 3
[0094] The difference between this embodiment and embodiment 1 is that in step S1, polyvinyl alcohol is replaced with sodium lauryl sulfate;
[0095] The remaining steps and their parameters are as in Example 1, and porous carbon with secondary particle configuration and corresponding gas phase silicon carbon material are obtained. The physical and chemical index parameters are shown in Table 1.
[0096] Example 4
[0097] The difference between this embodiment and embodiment 1 is that in step S1, sucrose is replaced with corn starch;
[0098] The remaining steps and their parameters are as in Example 1, and porous carbon with secondary particle configuration and corresponding gas phase silicon carbon material are obtained. The physical and chemical index parameters are shown in Table 1.
[0099] Example 5
[0100] The difference between this embodiment and embodiment 1 is that in step S2, the carbonization temperature is 1100°C;
[0101] The remaining steps and their parameters are as in Example 1, and porous carbon with secondary particle configuration and corresponding gas phase silicon carbon material are obtained. The physical and chemical index parameters are shown in Table 1.
[0102] Example 6
[0103] The difference between this embodiment and embodiment 1 is that in step S3, carbon dioxide is replaced with water vapor;
[0104] The remaining steps and their parameters are as in Example 1, and porous carbon with secondary particle configuration and corresponding gas phase silicon carbon material are obtained. The physical and chemical index parameters are shown in Table 1.
[0105] Example 7
[0106] The difference between this embodiment and embodiment 1 is that in step S1, sucrose is replaced by cellulose, polyvinyl alcohol is replaced by maleic anhydride, and the amount of maleic anhydride added is 20 g;
[0107] The remaining steps and their parameters are as in Example 1, and porous carbon with secondary particle configuration and corresponding gas phase silicon carbon material are obtained. The physical and chemical index parameters are shown in Table 1.
[0108] Example 8
[0109] The difference between this embodiment and embodiment 1 is that in step S1, sucrose is replaced by phenolic resin, polyvinyl alcohol is replaced by sodium hexametaphosphate, and the amount of sodium hexametaphosphate added is 25 g;
[0110] The remaining steps and their parameters are as in Example 1, and porous carbon with secondary particle configuration and corresponding gas phase silicon carbon material are obtained. The physical and chemical index parameters are shown in Table 1.
[0111] Example 9
[0112] The difference between this embodiment and embodiment 1 is that in step S1, polyvinyl alcohol is replaced with polyvinyl pyrrolidone, and the amount of polyvinyl pyrrolidone added is 25 g;
[0113] The remaining steps and their parameters are as in Example 1, and porous carbon with secondary particle configuration and corresponding gas phase silicon carbon material are obtained. The physical and chemical index parameters are shown in Table 1.
[0114] Comparative Example 1
[0115] The difference between this comparative example and Example 1 is that in step S1, polyvinyl alcohol is not added;
[0116] The remaining steps and their parameters are as in Example 1, and porous carbon with a single particle configuration and corresponding gas-phase silicon-carbon material are obtained. The physical and chemical index parameters are shown in Table 1.
[0117] Compared with Example 1, in this comparative example, no secondary particle configuration can be formed because polyvinyl alcohol is not added.
[0118] Comparative Example 2
[0119] The difference between this comparative example and Example 1 is that in step S1, the amount of polyvinyl alcohol added is 400 g;
[0120] The remaining steps and their parameters are as in Example 1, and porous carbon with secondary particle configuration and corresponding gas phase silicon carbon material are obtained. The physical and chemical index parameters are shown in Table 1.
[0121] Compared with Example 1, in this comparative example, since too much polyvinyl alcohol was added, the particle size of the primary particles was 0.25 μm.
[0122] Comparative Example 3
[0123] The difference between this comparative example and Example 1 is that in step S1, the amount of polyvinyl alcohol added is 1 g;
[0124] The remaining steps and their parameters are as in Example 1, and porous carbon with a single particle configuration and corresponding gas-phase silicon-carbon material are obtained. The physical and chemical index parameters are shown in Table 1.
[0125] Compared with Example 1, in this comparative example, since too little polyvinyl alcohol was added, the secondary particle configuration could not be formed.
[0126] Test Example 1
[0127] The physical and chemical index parameters of the average particle size D50, average sphericity of the primary particles, the average particle size D50, specific surface area, pore volume and particle size distribution K90 of the porous carbon with secondary particle configuration obtained in each embodiment and comparative example are shown in Table 1.
[0128] The particle size (μm) range of the material was tested using Dandong Better Laser Particle Sizer BT-9300ST;
[0129] The specific surface area (m² / g) of the material was tested using JW-DX dynamic adsorption specific surface area meter.
[0130] Field emission scanning electron microscopy (SEM) (JSM-7800F) was used to analyze the morphology and pattern processing of the materials;
[0131] The XRD diffractometer (Panalytical X'PERT PRO MPD, Netherlands) was used to analyze the phase of the material and determine the grain size of the material;
[0132] The pore volume of the material was tested using the American Quantachrome Autosorb IQ3.
[0133] Table 1
[0134]
[0135] It can be seen from Table 1 that the type of additives, their addition amounts, and the type of carbon source have a great influence on the particle size of the primary particles; it can be seen from the data of Examples 1, 2, and 4 that as the molecular weight of the carbon source gradually increases, the particle size of the primary particles also gradually increases; it can be seen from the data of Examples 1 and 3 that, at the same addition ratio, the particle size of the primary particles formed by using sodium dodecyl sulfate as an additive is smaller; in Comparative Example 1, since no additives were added, a secondary particle configuration could not be formed; in Comparative Example 2, since more additives were added, the particle size of the primary particles was only 0.25 μm; in Comparative Example 3, since there were fewer additives, a secondary particle configuration could not be formed.
[0136] Test Example 2
[0137] The performance of the gas phase silicon carbon materials obtained in each embodiment and comparative example was tested, and the results are shown in Table 2.
[0138] The specific surface area (m² / g) of the material was tested using JW-DX dynamic adsorption specific surface area meter.
[0139] Silicon-carbon material, conductive carbon black and binder are mixed in pure water at a mass ratio of 94.5:1.5:4, homogenized, and the solid content is controlled to be 48wt%, coated on a copper foil current collector, vacuum-baked at 100°C for 8h, pressed and formed, and then punched to prepare a negative electrode sheet;
[0140] The button half-cell was assembled in a glove box filled with argon. The counter electrode was a metal lithium sheet, the separator used was PE, and the electrolyte was 1 mol / L LiPF6 EC / DMC (Vol 1:1).
[0141] Carry out charge and discharge test on button batteries, the test process is 0.1C DC to 0.005V, 0.05C DC to0.005V, 0.02C DC to 0.005V, Rest 10min, 0.1C CC to 1.5V;
[0142] The first reversible capacity and efficiency of silicon-carbon materials were measured;
[0143] Among them, the button battery testing equipment is the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.
[0144] The silicon-carbon material is tested for its first reversible capacity by the above-mentioned charge-withdrawal test method, and then a certain amount of the same graphite negative electrode is mixed according to calculation, and the secondary particle silicon-carbon material is mixed to 600±5mA·h / g, abbreviated as S600;
[0145] The S600 mixed material, conductive carbon black and binder (mass ratio 92:2:6) were homogenized in pure water, the solid content was controlled to 48wt%, and the mixture was coated on a current collector with a copper foil as the substrate, and then vacuum-baked at 90°C for 8h, pressed by a roller press, and then sliced by a slicing device to prepare a negative electrode sheet; the thickness of the negative electrode sheet was measured by a micrometer and recorded as T1, and the thickness of the substrate was measured as T2, and the data were recorded;
[0146] Assemble button half-cells in an argon-filled glove box, with the counter electrode being a metal lithium sheet, the separator being a PE material, and the electrolyte being 1 mol / L LiPF6 EC / DMC (Vol 1:1); perform charge and discharge tests on the button cell, with the test process being 0.1CDC to 0.005V, 0.05C DC to 0.005V, 0.02C DC to 0.005V, Rest 10min, 0.1C CC to1.5V, 0.1C DC to 0.005V, 0.05C DC to 0.005V, 0.02C DC to 0.005V; measure the first reversible capacity and efficiency of the negative electrode material;
[0147] The battery is disassembled, and the thickness of the negative electrode material obtained by the disassembly is detected and recorded as T3; the first full-charge expansion data of the negative electrode material is calculated according to the formula F=(T3-T1) / (T1-T2), and F is the first full-charge expansion rate;
[0148] The button cell testing equipment is the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.; the slicing equipment is the MSK-T10 button half-cell slicing equipment of Kejing; the micrometer detection equipment is the Japanese Mitutoyo 293-100-10; and the rolling equipment is the MSK-HRP-05 button half-cell slicing equipment of Kejing.
[0149] The silicon-carbon material powder is mixed with the graphite negative electrode (mass ratio is 10~80:20~90) to obtain a mixed negative electrode powder, and then the negative electrode powder, Super p and BP-7 are mixed in pure water at a mass ratio of 92:4:4, and the solid content is controlled at 48wt%. After slurrying, it is coated on a current collector with a copper foil as the substrate, placed in a vacuum baking oven at 80℃-100℃ for vacuum baking for 4h-8h, and the pole piece is cold pressed with a commercial roller pressing equipment of Kejing, and the pole piece is sliced into small discs with a diameter of 15mm-22mm using a commercial slicing equipment of Kejing to prepare a silicon composite negative electrode pole piece; commercial 523 positive electrode material, SP and PVDF (polyvinylidene fluoride) are mixed with an appropriate amount of NMP (N-methyl pyrrolidone) solvent, control the solid content to 55wt%, apply the mixed slurry on the current collector with aluminum foil as the substrate, place it in a vacuum oven at 90℃-120℃ for vacuum baking for 4h-8h, use Kejing commercial roller pressing equipment to cold press the pole piece, use Kejing commercial slicing equipment to slice the pole piece into small discs with a diameter of 15mm-22mm to prepare the positive pole piece; dry it at 85℃ vacuum (-0.1MPa) for 8h, weigh and calculate the weight of the active material; the separator used is PE, and the electrolyte is 1mol / L LiPF6 EC / DMC (Vol 1:1); assemble it into a CR2430 button-type full battery in a glove box;
[0150] Leave the button cell at room temperature for 2h-6h, and use 0.1C to 0.005V, 0.05Cto 0.005V, 0.02C to 0.005V, 0.1C to 1.5V, 0.2C to 0.005V, 0.2C to 1.5V, 0.5C to0.005V, 0.5C to 1.5V, 1C to 0.005V, 0.5C to 1.5V, 2C to 0.005V, and 0.5C to 1.5V to perform charge and discharge on the Blue Electric test system, and then calculate the capacity at different charge rates: rate retention rate = charge capacity at different rates / first charge capacity.
[0151] Table 2
[0152]
[0153] The first charge and discharge curve of the lithium button cell made of gas phase silicon carbon material obtained in Example 1 is shown in Figure 3 The first charge and discharge dQ / dV curve of the lithium button cell made of the gas phase silicon carbon material obtained in Example 1 is shown in Figure 4 .
[0154] It can be seen from Table 2 that the gas-phase silicon-carbon material obtained in the embodiment of the present invention has a higher first reversible capacity and a higher rate retention rate due to the secondary particle configuration. In the lithium-ion battery test system, the first reversible capacity can reach more than 1850 mA·h / g, the first efficiency can reach more than 92%, the S600 first expansion rate is less than 34%, and the charging rate 2C / 0.1C can also reach more than 94%; the single-particle configuration gas-phase silicon-carbon materials obtained in Comparative Examples 1 and 3 have larger expansion and lower rate, mainly because the main particles are larger and have no secondary particle structure; although the gas-phase silicon-carbon material obtained in Comparative Example 2 has a secondary particle configuration, its first efficiency is lower, mainly because the particle size of the primary particles is too small.
[0155] By comparing the data of each embodiment and the comparative example, it can be seen that the particle size and type of the primary particles have a great influence on the expansion and rate of the silicon-carbon material; from the data of Examples 1-4, it can be seen that with the increase of the primary particle size, the initial expansion rate of S600 increases significantly and the rate also decreases slightly.
[0156] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing porous carbon with secondary particle configuration, characterized in that: The following steps are involved: (a) subjecting the carbon source to polymerization reaction to generate primary particles, which are then fused to obtain secondary particles of hard carbon precursor; The D50 particle size of the primary particles is 0.6 μm to 7.5 μm; The merging method comprises the following steps: The incompletely solidified primary particles are caused to collide with each other under stirring, so that the primary particles are melted; (b) the step (a) of the secondary particles of the hard carbon precursor is first pyrolyzed and carbonized, and then activated to obtain the secondary particle configuration of the porous carbon; The carbon source comprises at least one of glucose, fructose, galactose, lactose, sucrose, maltose, rice starch, mung bean starch, wheat starch, cassava starch, corn starch, cellulose and phenolic resin; The additives used in the polymerization reaction include at least one of maleic anhydride, hydroxymethyl cellulose, sodium hexametaphosphate, sodium lauryl sulfate, polyvinyl alcohol, hexadecyltrimethylammonium bromide and polyvinyl pyrrolidone; The amount of the additive is 0.01% to 0.5% of the weight of the carbon source; The polymerization reaction temperature is 150°C to 350°C; The polymerization reaction pressure is 2Mpa~8Mpa.
2. The preparation method according to claim 1, characterized in that: The particle size of the primary particles is 20% to 50% of the particle size of the secondary particles; The average sphericity of the primary particles is 0.6-1.
0.
3. The preparation method according to claim 1, characterized in that: The temperature of the pyrolysis carbonization is 800°C to 1400°C, and the time of the pyrolysis carbonization is 1h to 12h; The activation treatment method includes at least one of a physical activation method and a chemical activation method; The gas used in the physical activation method includes at least one of water vapor, air and carbon dioxide.
4. A porous carbon with a secondary particle configuration prepared by the preparation method according to any one of claims 1 to 3.
5. Use of the porous carbon with secondary particle configuration as claimed in claim 4 in gas phase silicon carbon materials.
6. The use according to claim 5, characterized in that: The specific surface area of the porous carbon of the secondary particle configuration is 700 m 2 / g~2000m 2 / g, pore volume is 0.3cm 3 / g~1.2cm 3 / g.
7. The use according to claim 5, characterized in that: The D50 particle size of the porous carbon of the secondary particle configuration is 3 μm to 15 μm; The particle size distribution K90 of the porous carbon with the secondary particle configuration is 0.8~1.
8.
8. A gas phase silicon carbon material, characterized in that: It is formed by depositing nano-silicon on the porous carbon with the secondary particle configuration as described in claim 4.
9. Use of the gas phase silicon carbon material according to claim 8 in a lithium ion secondary battery.
Citation Information
Patent Citations
Biomass-based porous carbon material, preparation method and application of biomass-based porous carbon material in separation of 1, 3-butadiene from C4 olefin mixture
CN112499628A